Antioxidant and laxative effects of taurine-xylose, a synthetic taurine-carbohydrate derivative, in loperamide-induced constipation in Sprague-Dawley rats - Jo, Hee Geun; Kim, Min Ji; Moon, Bo Yeong; Cheong, Sun Hee (Journal of exercise nutrition & biochemistry, 2019)
In this study, we examined the in vitro antioxidant activities and laxative effects of taurine-xylose (T-X), a synthetic taurine-carbohydrate derivative, in a rat model of constipation induced by loperamide. The animals were divided into four treatment groups: normal untreated rats (NOR group), loperamide-treated control rats (CON group), loperamide and taurine-xylose (15 mg/kg)-treated rats (T-X group), and loperamide and commercial Dulcolax S (5.5 mg/kg)-treated rats (DS group). In the present study, T-X exhibited potent reducing power and free radical scavenging activities for DPPH (1,1-diphenyl-2-picrylhydrazyl) and ABTS+ (2,2'-azino-bis (3-ethylbenzothiazoline 6-sulfonic acid ammonium salt) radicals. The laxative effects of T-X were dependent on food, body weight, fecal properties, gastrointestinal transit (GIT) ratio, and serum metabolic parameters. In the T-X group, the number, wet weight, and water content of fecal pellets were noticeably increased compared to those in the loperamide-induced group. T-X treatment significantly increased the activities of hepatic antioxidant enzymes, including those of glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT), relative to those in loperamide-induced constipated rats. Furthermore, the GIT ratio and loperamide-induced metabolic parameters in serum, including gastrin (GAS), motilin (MTL), and somatostatin (SS) levels, were significantly improved by T-X treatment. These results suggest that taurine-xylose exerts antioxidant activities and laxative effects on loperamide-induced constipation by promoting gastrointestinal motility.